Arbuscular mycorrhizal interaction associated with a botanical garden in the tropics of Mexico - José Alberto Gío-Trujillo; Carlos J. Alvarado-López (Current Research in Microbial Sciences)
Botanical gardens, areas for vegetation conservation, have become important reservoirs of beneficial soil microbiota, mainly as a source of microbial inoculum for agricultural purposes. Shrubby mycorrhizal fungi (AMF), an important genetic resource of tropical soils, have a high potential for agricultural production, generally used as inoculant medium that provides better yield, productivity and physiological response to crops. This research study explores the presence of AMF in a botanical garden, composed of four areas: cactarium collection, epiphytes and ornamental collection, tropical forest area and coastal zone. Each area is composed of plants representative of its ecosystem. For the study, a random systematic model was used, with nine samples per site at a depth of 20 cm. A physicochemical characterization of the soils was developed. The extraction of AMF spores was carried out by wet sieving and centrifugation in 60% sucrose. The spores were identified by taxon. The results indicate a total of 379 AMF spores identified in the study area. The highest spore incidence was recorded in the tropical forest area with a total of 161 (53.67±5.51) spores extracted, followed by the coastal zone and cactus collection area with 78 (26.00±9.64) and 73 (24.33±4.73) spores in total. In the study two taxa were identified, Glomeraceae and Gigasporaceae. The taxon Glomeraceae is also considered to be the most representative (highest abundance and frequency) of the study. In conclusion, botanical gardens, by their extructure (plant composition) and management can be taken into account as important ecosystems reservoirs and source of viable microbial genetic material for the bioprospecting of beneficial soil genotic resources (rhizophiles and endophylls) for use in modern agriculture and sustainable food production systems.